THE INFLUENCE OF RELIGIOSITY, ACCOUNTABILITY ON MUZAKKI'S INTEREST IN PAYING ZAKAT IN ZAKAT INSTITUTIONS WITH TRUST AS AN INTERVENING VARIABLE: Shariah Fintech - Sudah, Moh. (Journal Financial, Business and Economics, 2024)
The aim of this research is to analyze the factors of religiosity, accountability and trust on people's interest in paying zakat at zakat institutions, and to analyze whether religiosity and accountability have an influence through trust on people's interest in paying zakat at zakat institutions. The research method used is a quantitative approach. This research found that the results of religiosity influence interest in paying zakat at zakat institutions, the accountability variable does not influence interest in paying zakat at zakat institutions, religiosity and accountability influence trust, religiosity and accountability influence interest in paying zakat at zakat institutions through the trust variable. It can be concluded that trust can strengthen religiosity and accountability towards interest in paying zakat at zakat institutions, but accountability has no effect on interest in paying zakat at zakat institutions if it does not coincide with other variables